Intrinsic Motivation in Two Exercise Interventions: Associations With Fitness and Body Composition - Thøgersen-Ntoumani, Cecilie; Shepherd, S.; Ntoumanis, Nikos; Wagenmakers, A.; Shaw, C. (American Psychological Association Inc., 2015)
Objective: To examine the motivational process through which increases in aerobic capacity and decreases in total body fat are achieved during high-intensity intermittent training (HIT) and moderate-intensity continuous training (MICT) interventions. Method: Eighty-seven physically inactive adults (65% women, age = 42 ± 12, BMI = 27.67 ± 4.99 kg/m2) took part in a 10-week randomized intervention testing group-based HIT, operationalized as repeated sprints of 15-60 s interspersed with periods of recovery cycling = 25 min/session, 3 sessions/wk-1, or MICT, operationalized as cycling at constant workload of 65% maximum aerobic capacity (VO2max, 30-45 min/session-1, 5 sessions/wk-1. Assessments of VO2max and total body fat were made pre- and postintervention. Motivation variables were assessed midintervention and class attendance was monitored throughout. Path analysis was employed, controlling for treatment arm and baseline values of VO2max and total body fat. Results: The 2 groups differed in adherence only, favoring HIT. Baseline VO2max predicted intrinsic motivation midintervention. Intrinsic motivation predicted program adherence, which in turn predicted increases in VO2max and decreases in total body fat by the end of the study. Conclusion: Intrinsic motivation in HIT and MICT is positively linked to adherence to these programs, which can facilitate improvements in fitness and body composition.